Lumbar extensor muscle force control is associated with disability in people with chronic low back pain. (July 2017) - Pranata, Adrian; Perraton, Luke; El-Ansary, Doa; Clark, Ross; Fortin, Karine; Dettmann, Tim; Brandham, Robert; Bryant, Adam
Abstract: Background: The ability to control lumbar extensor force output is necessary for daily activities. However, it is unknown whether this ability is impaired in chronic low back pain patients. Similarly, it is unknown whether lumbar extensor force control is related to the disability levels of chronic low back pain patients. Methods: Thirty-three chronic low back pain and 20 healthy people performed lumbar extension force-matching task where they increased and decreased their force output to match a variable target force within 20%–50% maximal voluntary isometric contraction. Force control was quantified as the root-mean-square-error between participants' force output and target force across the entire, during the increasing and decreasing portions of the force curve. Within- and between-group differences in force-matching error and the relationship between back pain group's force-matching results and their Oswestry Disability Index scores were assessed using ANCOVA and linear regression respectively. Findings: Back pain group demonstrated more overall force-matching error (mean difference = 1.60 [0.78, 2.43], P  < 0.01) and more force-matching error while increasing force output (mean difference = 2.19 [1.01, 3.37], P  < 0.01) than control group. The back pain group demonstrated more force-matching error while increasing than decreasing force output (mean difference = 1.74, P  < 0.001, 95%CI [0.87, 2.61]). A unit increase in force-matching error while decreasing force output is associated with a 47% increase in Oswestry score in back pain group (R 2  = 0.19, P  = 0.006). Interpretation: Lumbar extensor muscle force control is compromised in chronic low back pain patients. Force-matching error predicts disability, confirming the validity of our force control protocol for chronic low back pain patients. Highlights: Lumbar extensor muscle force control is impaired in people with chronic low back pain. The ability to accurately increase, but not decrease, force output is impaired in people with chronic low back pain. Impairment in lumbar extensor muscle force control is associated with disability in people with chronic low back pain.